Making an Android-Based Educational Game on Chemical Equilibrium Material - Tika Ramdina Putri; Saepudin Rahmatullah; Ferli Septi Irwansyah (Gunung Djati Conference Series, 2023)
This study aims to describe the appearance of the media, analyze the results of the validation test, and analyze the results of the feasibility of an android-based educational game on chemical equilibrium material so that it can be used in learning. The method used in this study is the Design Based Research (DBR) method with the ADDIE model. The data collection technique used a validation questionnaire and a feasibility questionnaire. The validation test was carried out on two Chemistry Education Lecturers at UIN Sunan Gunung Djati Bandung and one chemistry teacher at MAN 1 Subang by obtaining an average rcount of 0.79 so that the media was declared valid. The feasibility test for students of class XII IPA MAN 1 Subang as many as 16 people who have studied chemical equilibrium obtained an average percentage value of 79.63% so that the media is feasible to use